2014
DOI: 10.1007/s12035-014-8877-4
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Spatial Memory, Learning, and Motor Function During Normal Aging Is Accompanied by Changes in Brain Presenilin 1 and 2 Expression Levels

Abstract: Mutations in presenilin (PS) proteins cause familial Alzheimer’s disease. We herein tested the hypothesis that the expression levels of PS proteins are differentially affected during healthy aging, in the absence of pathological mutations. We used a preclinical model for aging to identify associations between PS expression and quantitative behavioral parameters for spatial memory and learning and motor coordination. We identified significant changes of PS protein expression in both cerebellum and forebrain tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 61 publications
(74 reference statements)
0
18
0
Order By: Relevance
“…While it is well known that the mutation of PS1 genes increases Ab formation, the role of wild-type PS1 in the brain is less explored and controversial. A decrease in PS1 occurred in the brain of aged mice (Thakur and Ghosh, 2007;Kaja et al, 2015), suggesting the role of PS1 depletion in aging. On the other hand, an increase in PS1 occurred in the hippocampus of aged mice that exhibited premature memory loss and a normal cDNA sequence of PS1 (Kumar et al, 2009).…”
Section: Introductionmentioning
confidence: 92%
“…While it is well known that the mutation of PS1 genes increases Ab formation, the role of wild-type PS1 in the brain is less explored and controversial. A decrease in PS1 occurred in the brain of aged mice (Thakur and Ghosh, 2007;Kaja et al, 2015), suggesting the role of PS1 depletion in aging. On the other hand, an increase in PS1 occurred in the hippocampus of aged mice that exhibited premature memory loss and a normal cDNA sequence of PS1 (Kumar et al, 2009).…”
Section: Introductionmentioning
confidence: 92%
“…In contrast to endogenous PS1, PS2 was mainly found as the full-length protein in human and mouse brains [5,6]. During embryonic development [7], neuron maturation [6], and aging [8], PS1 expression was either constant or decreased while PS2 expression increased, thus indicating their distinct regulatory functions.…”
Section: Introductionmentioning
confidence: 99%
“…One early study investigated PS mRNA and protein levels in the cortex and found decreased PS1 and increased PS2 expression in 15 months old compared to 6 months old mice [18] . A more recent study focused on both forebrain and cerebellar PS expression levels in both young, 6 months old, and aged, 24 months old, mice that had been behaviorally characterized to provide a detailed quantification of their cognitive and motor performance [19] . In rodent models, cognitive and motor impairment can be quantified using a variety of well-established behavioral paradigms including the swim maze test and the bridge walking task [20, 21] .…”
mentioning
confidence: 99%
“…In rodent models, cognitive and motor impairment can be quantified using a variety of well-established behavioral paradigms including the swim maze test and the bridge walking task [20, 21] . PS protein expression was highly correlated with performance in behavioral paradigms for motor function, memory, and learning [19] . Specifically, PS1 levels were decreased while PS2 levels were increased in aged mice compared with young controls and with increasing impairment of their cognitive and motor performance [19] .…”
mentioning
confidence: 99%
See 1 more Smart Citation